DISTRESS PSIKOLOGI PADA RESIKO KERENTANAN BUNUH DIRI - Husni, Husni; Asmawati, Widia Lestari , (JURNAL MEDIA KESEHATAN, 2018)
Staying in prisons, making space for prisoners is restricted and isolated fromsociety, confined and isolated situation can be a stressor that causes stress. The purpose ofresearch is known relationship with psychological distress vulnerability adolescent suicidalinmates in prisons Class II A Bengkulu. Type descriptive analytic research withcross sectional approach. The sample in this study were all teenagers who inhabit prisoninmates Class II A Bengkulu in November 2015, as many as 49 prisoners. Collecting datausing questionnaires. The data analysis was conducted quantitative univariate, bivariate,and multivariate analysis. The result showed a small fraction of prisoners suffered psychologicaldistress, most inmates aged ≤ 18 years, nearly all prisoners gender to male,mostly poorly educated prisoners, a fraction highly vulnerable inmates committed suicide.There is no significant relationship between psychological distress with the vulnerabilityof suicide on inmates in prisons Class II A Bengkulu. The need for counseling tothe inmates of prisons in addressing various problems with doing something positivethereby prison occupants will be able to receive him at the moment, and look at everythingpositively.